Characteristics of three lower limb joint kimetics during the rebound jump in female athletes - Zushi, A.; Zushi, K.; Yoshida, T. (ISBS Proceedings Archive (Michigan), 2021)
The aim of this study was to describe the lower limb muscle strength and power exertion characteristics of female athletes during the rebound jump (RJ) test. Forty-eight female soccer and basketball players performed the test, while the Quick Motion Analysis System was used to calculate joint kinetics (torque, power, and work of the three lower limb joints) in real time with high precision. A high correlation was found between the RJ index and contact time, jump height. In addition, a low correlation was found between jump height and contact time. However, the mechanical variables related to contact time and jump height were different. Therefore, for female athletes, the ability to shorten the contact time and the ability to obtain a jump height are considered independent abilities.